BUILDING SECURE AUTOMOTIVE IOT APPLICATIONS developing robust IoT solutions for next-gen automotive software - Oka, Dennis Kengo; Nadahalli, Sharanukumar; Yost, Jeff; Bojanki, Ram Prasad (Packt Publishing Ltd., 2024)
Enhance your automotive IoT design and development knowledge by learning vehicle architectures, cybersecurity best practices, cloud applications, and software development processes Key Features Explore modern vehicle architectures designed to support automotive IoT use cases Discover cybersecurity practices and processes to develop secure automotive IoT applications Gain insights into how cloud technologies and services power automotive IoT applications Purchase of the print or Kindle book includes a free PDF eBook Book Description Software-defined vehicles, equipped with extensive computing power and connectivity, are unlocking new possibilities in automotive Internet of Things (IoT) applications, creating a critical need for skilled software engineers to lead innovation in the automotive sector. This book equips you to thrive in this industry by learning automotive IoT software development. The book starts by examining the current trends in automotive technology, highlighting IoT applications and key vehicle architectures, including the AUTOSAR platform. It delves into both classic and service-oriented vehicle diagnostics before covering robust security practices for automotive IoT development. You'll learn how to adhere to industry standards such as ISO/SAE 21434, ASPICE for cybersecurity, and DevSecOps principles, with practical guidance on establishing a secure software development platform. Advancing to the system design of an automotive IoT application, you'll be guided through the development of a remote vehicle diagnostics application and progress through chapters step by step, addressing the critical aspects of deploying and maintaining IoT applications in production environments. By the end of the book, you'll be ready to integrate all the concepts you've learned to form a comprehensive framework of processes and best practices for embedded automotive development. What you will learn Explore the current automotive landscape and IoT tech trends Examine automotive IoT use cases such as phone-as-a-key, predictive maintenance, and V2X Grasp standard frameworks such as classic and adaptive AUTOSAR Get to grips with vehicle diagnostic protocols such as UDS, DoIP, and SOVD Establish a secure development process and mitigate software supply chain risks with CIAD, RASIC, and SBOM Leverage ASPICE and functional safety processes for industry standards compliance Understand how to design, develop, and deploy an automotive IoT application Who this book is for This book is for embedded developers and software engineers working in the automotive industry looking to learn IoT development, as well as IoT developers who want to learn automotive development. A fundamental grasp of software development will assist with understanding the concepts covered in the book.
Keywords: Automotive computers; Software engineering; Software architecture; Internet of things; Application software -- Development; Embedded computer systems; Automobiles -- Design and construction; Ordinateurs de bord; Génie logiciel; Architecture logicielle; Internet des objets; Logiciels d'application; Développement; Systèmes enfouis (Informatique); Automobiles; Conception et construction